2022
DOI: 10.1007/s12144-022-02776-x
|View full text |Cite
|
Sign up to set email alerts
|

International students challenges during the COVID-19 pandemic in a university in the United States: A focus group study

Abstract: Research suggests that the COVID-19 pandemic has deeply impacted college students. However, very few studies have attended to the specific plight of international students . The purpose of this study was to document challenges international students may have encountered while studying in the United States during the pandemic. Focus groups (N = 4; 13 students total) were conducted with students who were ≥ 18 years of age, enrolled at least part-time, on an F1 visa, and non-resident alien, who did not have paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…The authors suggested that the differences in the prevalence of depression and anxiety are attributable to insufficient attention being paid to prevention of the pandemic at the initial stage of the outbreak [ 54 ]. A qualitative study at West Virginia University in the USA revealed that international students’ sentiment of homesickness and loneliness was further accentuated by the uncertainty due to travel restrictions [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that the differences in the prevalence of depression and anxiety are attributable to insufficient attention being paid to prevention of the pandemic at the initial stage of the outbreak [ 54 ]. A qualitative study at West Virginia University in the USA revealed that international students’ sentiment of homesickness and loneliness was further accentuated by the uncertainty due to travel restrictions [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that, for international university students in many countries, the sudden closure of some international borders not only severely disrupted their learning and social activities but may have also impacted their sense of safety and belonging, leading to higher rates of psychological distress and making them particularly vulnerable to housing and food insecurity [ 25 , 26 ]. A qualitative study on Vietnamese students in the USA, for example, found that high levels of uncertainty and the impact of lockdown orders were likely to have substantial consequences in terms of psychological distress for these students [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Worthy yet mostly neglected is the provision of psychological support services for interns as international students is what the present study underlined. Recent studies reported COVID-19 results in weak social interaction and relationship that deteriorates mental states (Rudnik et al, 2020), homesickness (Rathakrishnan et al, 2021) of international students and generally jeopardize their academic performance (Mbous, Mohamed, & Rudisill, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our discussions above have critically examined how mainland Chinese students evaluated overseas study during and after the COVID-19 crisis, showing growing interest of Chinese students making Asia their future destination for studying abroad, especially when they were becoming more concerned about the public health conditions in traditional destinations based in Europe, the UK, and the US. The motivations and desires of Chinese students choosing overseas learning would have been affected by the new geopolitics and different kinds of “cultural shocks,” particularly when Asian students were reported being discriminated against and stigmatized after the outbreak of the COVID-19 pandemic when studying abroad (Mbous et al, 2022 ; Mok and Zhang, 2022 ).…”
Section: Discussionmentioning
confidence: 99%